Optimizing Arabic Writing Skills Based On TPACK Learning And Poster Media - Zainul Arifin; Suci Ramadhanti Febriani; Arifka Mahmudi; Kddour Guettaoui Bedra (Ijaz Arabi Journal of Arabic Learning, 2025)
Arabic writing skills in higher education are a forum for increasing student creativity. Through the media of posters and descriptions of cultural texts, students can develop their imagination in written form. However, there is a need for a TPACK (Technological Pedagogical Content Knowledge) learning model as a systematic flow in implementing learning Arabic writing skills. On that basis, this research aims to analyze TPACK-based learning practices through multicultural texts with poster media. This research used a mixed-method design with research subjects of 122 fifth-semester Arabic Language Education study program students at UIN Imam Bonjol Padang—data collection techniques through tests, observation, interviews, and documentation with a mixed-method based analysis. The research results reveal that learning writing skills using multicultural texts and poster media can improve students' ability to write Arabic, which is characterized by the diversity of phrases, sentences, and paragraphs through descriptions of the culture found in Indonesia. This research recommends further research to analyze the forms of phrases that develop among students.